Morphological and physiological response of syzygium myrtifolium (Roxb.) Walp. to paclobutrazol - Ahmad Nazarudin Mohd Roseli; Tsan, Fui Ying; Mohd Fauzi Ramlan (Universiti Kebangsaan Malaysia, 2012)
Syzygium myrtifolium (Roxb.) Walp. is a popular landscape plant in Malaysia. This species is always planted as hedge plant and topiary. However, it requires frequent trimming to maintain its form and aesthetic functions as it grows vigorously. Conventional trimming technique by using trimming shear or trimming machine is currently practiced in landscape maintenance which is time consuming, labour intensive and costly. Therefore, a study was conducted to investigate the effects of a plant growth retardant, paclobutrazol, on the growth and physiological response of S. myrtifolium. The plants were planted in polyethylene bags sized 33 cm in height × 27 cm in diameter and filled with soil, organic matter and sand (3:2:1). Paclobutrazol at rates of 0, 1.25, 2.50 and 3.75 g L-1 were soil drenched at 30 days after the plants were trimmed and new shoots were produced. Paclobutrazol significantly reduced plant height and leaf area but increased the leaf area index. Reduced photosynthetic rates were recorded with the treated plants as compared to the control plants. In addition, paclobutrazol at 3.75 g L-1 significantly reduced the transpiration rate as compared with the control plants and plants treated with 1.25 g L-1 of paclobutrazol. However, stomatal conductance was not affected significantly by paclobutrazol. The growth inhibition effect of paclobutrazol reduced the trimming activity in S. myrtifolium. Chlorophyll fluorescence measurement indicated that physiological processes in the paclobutrazol-treated plants were not affected. Paclobutrazol is concluded to offer a better approach in maintaining the growth of S. myrtifolium.